Analyzing the effect of accountability, government characteristics, and citizen participation on the financial performance of Philippine cities - De Nobili, Lou Brad N. (Animo Repository, 2021)
In celebration of the 30th anniversary of the enactment of the Local Government Code of 1991, there is a need to re-assess local government performance in terms of achieving the goals of the landmark legislation which is decentralization and self-sufficiency. Attaining such goals entails local governments providing programs and initiatives to improve their financial standing. A better understanding of the drivers of financial performance is therefore imperative in accomplishing the herculean task at hand. Taking into account the multitude of factors affecting financial outcomes, this study aims to determine how certain non-financial variables affect the city LGU’s financial performance. In pioneering the research in the Philippine context in exploring the effects of the non-financial variables on the city LGU financial performance, the researchers have incorporated 116 cities from 2011 to 2019 in utilizing the panel regression model. Such findings portray the varying effects and significance of accountability, government characteristics, and citizen participation on the locally sourced revenue, while only electoral activity posits a negative effect on a city LGU’s efficiency ratio. In assessing the results, the researchers have presented insights in pursuing sound and competent governance to stimulate a stronger sense of accountability and public financial management across the nation. Keywords: accountability, government characteristics, citizen participation, LGU financial performance